2016
DOI: 10.1002/ajmg.b.32505
|View full text |Cite
|
Sign up to set email alerts
|

Genetic prion disease: Experience of a rapidly progressive dementia center in the United States and a review of the literature

Abstract: Although prion diseases are generally thought to present as rapidly progressive dementias with survival of only a few months, the phenotypic spectrum for genetic prion diseases (gPrDs) is much broader. The majority have a rapid decline with short survival, but many patients with gPrDs present as slowly progressive ataxic or parkinsonian disorders with progression over a few to several years. A few very rare mutations even present as neuropsychiatric disorders, sometimes with systemic symptoms such as gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 200 publications
3
101
1
2
Order By: Relevance
“…The main manifestations are progressive dementia, myoclonus twitches, and injury of pyramidal tract and extrapyramidal system. The main different diagnosis point of CJD and LE is the negative LGI1 antibody of CSF, 14-3-3 positive protein 19,20…”
Section: Discussionmentioning
confidence: 99%
“…The main manifestations are progressive dementia, myoclonus twitches, and injury of pyramidal tract and extrapyramidal system. The main different diagnosis point of CJD and LE is the negative LGI1 antibody of CSF, 14-3-3 positive protein 19,20…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence is 1 to 10/100,000,000, with onset typically in the 5th decade (51.5 ± 12.8 years; although, in recent reports, it is 41 ± 14 years) . The average illness duration is 40 to 50 months (44 ± 12.1 months, median = 40) …”
mentioning
confidence: 97%
“…1 Thus, GSS should be considered a chronic, rather than a subacute, progressive disorder. Previous studies suggested that cognitive and behavioral symptoms were more common in sCJD, whereas movement disorders, specifically gait ataxia, were most common as initial features in GSS.…”
Section: Discussionmentioning
confidence: 99%